18F-FDG PET/MR imaging of lymphoma nodal target lesions: Comparison of PET standardized uptake value (SUV) with MR apparent diffusion coefficient (ADC) - Bernstine, Hanna (Medicine (Baltimore), 2018)
To compare positron emission tomography (PET) standardized uptake value (SUV) with magnetic resonance (MR) apparent diffusion coefficient (ADC) of nodal target lesions in patients with (18)F-fluoro-2-deoxyglucose (FDG)-avid lymphomas by simultaneous PET/MR. Patients with histologically proven Hodgkin and non-Hodgkin lymphoma underwent PET/MR limited field of view of FDG-avid target nodal lesions. For PET images, a region of interest (ROI) was drawn around the target nodal lesion and the SUVmax and SUVmean was measured. For MR ADC measurements a ROI was placed over the target nodal lesion on diffusion-weighted imaging (DWI) and ADCmin and ADCmean (mean ADC) values within the ROI were recorded. Thirty-nine patients (19 women, 20 men; 13 patients with Hodgkin lymphoma and 26 with non-Hodgkin lymphoma) were included in the analysis. Sixty-six nodal lesions detected by PET/CT (19 PET-negative and 47 PET-positive) were analyzed by PET/MR. PET/MR quantitative assessments showed that ADCmin and ADCmean were accurate for discriminating positive from negative nodal lymphoma, with an AUC of 0.927 and 0.947, respectively. The ROC curve analysis of ADCmean versus SUVmax and SUVmean was not statistically significant (difference=0.044, P = .08 and difference = 0.045, P = .07; respectively). A substantial inverse association was observed between ADCmean with SUVmean and SUVmax (rho = −0.611; −0.607; P < .0001, respectively). A moderate inverse association was found between ADCmin with SUVmean and SUVmax (rho = −0.529, −0.520; P < .0001, respectively). Interobserver variability of quantitative assessment showed very good agreement for all variables (ICC>0.87). A significant correlation between ADCs and SUVs is found in FDG avid lymphomas. ADCmean is not inferior to PET SUV in discriminating positive and negative nodal lymphomas. Further larger studies are warranted to validate quantitative PET/MR for lymphoma patient management.